2022
DOI: 10.33963/kp.a2022.0130
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade endotoxemia and NOX2 in patients with coronary microvascular angina

Abstract: Background: Endothelial dysfunction and oxidative stress were hypothesized to be involved in the pathogenesis of coronary microvascular angina (MVA). NADPH oxidase-2 (NOX2) activation could provoke increased oxidative stress and endothelial dysfunction, but data on MVA have not been provided yet.Aims: This study aimed to evaluate the interaction among NOX2 activation, serum lipopolysaccharide (LPS) levels, as well as oxidative stress production as potential causes of endothelial dysfunction in MVA patients. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…To the best of our knowledge, no description of an association among LPS, NOX2 and endothelial dysfunction has been reported in literature. An association among increased LPS, NOX2 and oxidative stress was already reported in other diseases, such as neurodegenerative ( Loffredo et al, 2020a ), neuropsychiatric ( Loffredo et al, 2020c ) or cardiovascular ( Loffredo et al, 2022b ) disorders.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…To the best of our knowledge, no description of an association among LPS, NOX2 and endothelial dysfunction has been reported in literature. An association among increased LPS, NOX2 and oxidative stress was already reported in other diseases, such as neurodegenerative ( Loffredo et al, 2020a ), neuropsychiatric ( Loffredo et al, 2020c ) or cardiovascular ( Loffredo et al, 2022b ) disorders.…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, the inhibition of NOX-2 decreased LPS-induced superoxide ( Joseph et al, 2017 ). Considering that LPS directly correlates with NOX2 ( Loffredo et al, 2022b ), it could play a role as a trigger of oxidative stress. The high levels of H2O2 together with the low levels of HBA, and the close relation with sNOX2 could indicate that systemic oxidative stress in CP and CAP derive from LPS-induced NADPH oxidase activation as hypothesised by previous studies ( Oliva et al, 2021b ; Petruk et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that LPS was increased in the systemic circulation of adult patients with acute myocardial infarction [ 12 , 22 ] and coronary microvascular angina [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…By binding to TLR4, LPS prompts the intracellular transcription of inflammatory pathways and NADPH oxidase activation [ 14 , 15 ], resulting in platelet activation, thrombosis and atherosclerosis [ 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between endothelial damage and endotoxemia has been investigated by Loffredo et al [55] who reported elevated LPS levels in patients with microvascular angina, which correlated inversely with serum nitric oxide and directly with serum endothelin 1. Similarly, enhanced LPS levels have been detected in patients with stable angina and myocardial infarction with a gradient increase from stable to unstable disease.…”
Section: Low-grade Endotoxemia and Cardiovascular Diseasementioning
confidence: 99%